2006
DOI: 10.1021/jp064071h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Networked Metallofullerenes of the Transition Metals

Abstract: A DFT investigation of substitutionally doped fullerenes MC59 of second- and third-row transition metals shows that their stability increases toward the right-hand side of the d-block. Whereas the structural deviation from that of C60 depends on the size of the metal atom, stability is governed by electronic properties of the transition metal atom. A range of MC59 compounds of group 6-8 metals are predicted to have sufficient stability for experimental observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The mechanism of formation is believed to involve formation of a fullerenetransition metal adsorbate complex, followed by insertion into the carbon framework [104]. Additionally, the synthesis of second-and third-row transition metal-doped fullerenes has been predicted to be attainable via reaction of the corresponding transition metal trichloride (or dichloride) in the presence of chlorine gas (Cl 2 ) and buckminsterfullerene (C 60 ) [105]. Theoretical studies also provide insight into the electronic properties of transition metal-doped fullerenes [106][107][108][109].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of formation is believed to involve formation of a fullerenetransition metal adsorbate complex, followed by insertion into the carbon framework [104]. Additionally, the synthesis of second-and third-row transition metal-doped fullerenes has been predicted to be attainable via reaction of the corresponding transition metal trichloride (or dichloride) in the presence of chlorine gas (Cl 2 ) and buckminsterfullerene (C 60 ) [105]. Theoretical studies also provide insight into the electronic properties of transition metal-doped fullerenes [106][107][108][109].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the stability of these compounds could depend on the degree of integration of the metal atom into the carbon network. However, significantly more stable metallofullerenes, MC 59 , are obtained for second-and third-row transition metals that are of roughly the same size as the early first-row metals (35), suggesting that the correlation between atomic radius and stability is accidental, or at least that size is not the primary cause. The variation in distortion seen between MC 59 cages of the different metals is significant ( Figure 1) and it is remarkable that this structural variation does not seem to have appreciable impact on metallofullerene stability.…”
Section: Resultsmentioning
confidence: 98%
“…We begin with the consideration that each Ta-Ta bond accounts for two Wannier centers ͑one for each FIG. 10. ͑Color online͒ ͑a͒ Wannier function centers around Ta site.…”
Section: Electron Localization Function and Localized Orbitalsmentioning
confidence: 99%
“…As a theoretical counterpart to experiments, density-functional theory ͑DFT͒ provides a well-suited and reliable approach to elucidate the relationship between the bonding properties of the fullerenes and the nature of the dopants. 3 However, while several studies of TM substitutional and endohedral heterofullerenes have been reported over the years, [4][5][6][7][8][9][10][11][12] the literature about the electronic structure of exohedral TM is nearly nonexistent. 11,13 The main purpose of this paper is to fill this gap by describing the electronic properties of Ta-doped exohedral heterofullerenes.…”
Section: Introductionmentioning
confidence: 99%